CHARACTERISTICS OF VOLCANIC ASH SOILS FROM SOUTHERN PART OF MT. TANGKUBAN PERAHU, WEST JAVA - YATNO, EDI; ZAUYAH, S. (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2005)
Three soil pedons developed on young andesitic volcanic ash with high mineral deposit and high P retention, granular soil structure, high porosity, and low bulk density, were differentiated based on their morphological, physical, chemical and mineralogical characteristics. Pedons 1 and 3 are discontinue or bisequm pedons characterized by the presence of more contrast colour and new buried materials on layer 4, while pedon 2 isrelatively younger than pedons 1 and 3. Mineralogical composition of pedons 1 and 3 is very different compared with pedon 2. Pedons 1 and 3 have high total porosity resulting in easy to the soil leaching. Pedon 2 with higher bulk density tends to be more compact although its soil texture is light, indicating soil character of Andisols from this young volcanic material. High P retention and low base saturation may bring about high Pfertilizer need. Pedons 1 and 3 have lower feldspar content as K sources compared with pedon 2, while the content of opaque minerals is higher in pedons 1 and 3 indicating more developed pedons. The top layer of pedon 1 has lower opaque minerals but higher hornblende than pedon 3 due to different land use. The presence of alophane minerals in pedon 1 and 3 can be detected from the results of Selective Dissolution Analysis, but they do not detected on X-ray diffraction patterns. In pedon 2, however, alophane minerals show convex diffraction patterns. Based oncharacteristics of their soil physics, chemistry, and mineralogy, pedons 1 and 3 were classified as Thaptic Hapludands, and pedon 2 as Typic Melanudands. The increase of P availability on the three pedons can be done by P fertilization and liming to accelerate substitution of Al-P to Ca-P and increase of soil pH.